Angels' flight - Singh, Nalini, 1977- (Singh, Nalini, 1977- Guild Hunter series., 2012)
A collection of four stories set in the world of the author's "Guild Hunter" novels includes "Angel's Wolf," in which a vampire becomes fascinated by the angel who rules Louisiana.